Investigation into the bottlenecks of conducting research in faculty of resource science and technology (FRST) - Chong, Christa (Universiti Malaysia Sarawak (UNIMAS), 2012)
University Malaysia Sarawak (UNIMAS) is one of the universities in Malaysia which aims to be a Research University (RO). A RU vision is to actively participate in new adventures of ideas, experiment with innovative methods, and take intellectual initiatives to further discover and expand the frontiers of knowledge. The mission of RU is to be an engine of growth of the nation where scholars and students exchange ideas as well as conduct research in a conducive environment that nurtures exploration and creativity discover knowledge and create wealth, leading towards an improved quality of life. The goals ofthe RU are to be a leader in innovation, to produce Nobel Prize winners, to produced world class research outputs, to generate high impact research publications, to secure research funds from indusUy and to attract and to graduate students of high standard. Faculty of Resource Science and Technology (FRST) is one of eight faculties in UNIMAS that actively participated in research activities. However, it is not easy to become a research university. The researchers in this faculty always encounter bottlenecks during their research. Therefore, it is crucial to identify what are the bottlenecks that encounter by the researchers in FRST in order to become a research university. From the survey, it is identified that funds, lack of materials and lacks of equipments is the most common bottlenecks. Hence, it is very important to find solution for the bottleneck in order for UNIMAS to become a research university.